Mouse Wnt1-CRE-RosaTomato Dental Pulp Stem Cells Directly Contribute to the Calvarial Bone Regeneration Process. (13th March 2019) - Collignon, Anne-Margaux; Castillo-Dali, Gabriel; Gomez, Eduardo; Guilbert, Thomas; Lesieur, Julie; Nicoletti, Antonino; Acuna-Mendoza, Soledad; Letourneur, Didier; Chaussain, Catherine; Rochefort, Gael Y.; Poliard, Anne
Abstract : Stem cells endowed with skeletogenic potentials seeded in specific scaffolds are considered attractive tissue engineering strategies for treating large bone defects. In the context of craniofacial bone, mesenchymal stromal/stem cells derived from the dental pulp (DPSCs) have demonstrated significant osteogenic properties. Their neural crest embryonic origin further makes them a potential accessible therapeutic tool to repair craniofacial bone. The stem cells' direct involvement in the repair process versus a paracrine effect is however still discussed. To clarify this question, we have followed the fate of fluorescent murine DPSCs derived from PN3 Wnt1-CRE - Rosa Tomato mouse molar (T-mDPSCs) during the repair process of calvaria bone defects. Two symmetrical critical defects created on each parietal region were filled with (a) dense collagen scaffolds seeded with T-mDPSCs, (b) noncellularized scaffolds, or (c) no scaffold. Mice were imaged over a 3-month period by microcomputed tomography to evaluate the extent of repair and by biphotonic microscopy to track T-mDPSCs. Histological and immunocytochemical analyses were performed in parallel to characterize the nature of the repaired tissue. We show that T-mDPSCs are present up to 3 months postimplantation in the healing defect and that they rapidly differentiate in chondrocyte-like cells expressing all the expected characteristic markers. T-mDPSCs further maturate into hypertrophic chondrocytes and likely signal to host progenitors that form new bone tissue. This demonstrates that implanted T-mDPSCs are able to survive in the defect microenvironment and to participate directly in repair via an endochondral bone ossification-like process. Stem Cells   2019;37:701–711 : Abstract : Wnt1-CRE-RosaTomato DPSC were implanted in a calvaria critical-sized defect and shown by microCT, biphotonic and immunohistochemical analyses to participate in bone repair through an endochondral process